NOGIRONLIKKA EGA BO‘LGAN BOLALARNING ME’YORIDA RIVOJLANAYOTGAN TENGDOSHLARI JAMOASIGA INTEGRATSIYASI - Tasbaeva, G.; Achilbayeva, L. (SCIENCE and SOCIETY, 2016)
The article is devoted to the study of the causes of disability in the development of children with deviations, their integration and explanation. The author of the article also studies the opinions of scholars and defectologists on the issues of upbringing and education of young generation.